Sources of Extradition Law in the Legal System of the European Union - Brodowski, Lidia (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The article discusses the activities, involving the creation and unification of the sources of extradition law and modernization undertaken in the institution of extradition within the European Union, aimed at creating a coherent and efficient system for fighting crime. It presents the evolution, that EU extradition law in the last decade was a subject to, which reflects the changes made in primary law, international agreements and the Acts signed by the institutions of the European Union. It provides an analysis of the existing extradition relations model within the European Union and its impact on initiatives to simplify and accelerate the extradition procedure undertaken outside the framework of the European Union.
Keywords: prawo ekstradycyjne; Unia Europejska; procedury; europejski nakaz aresztowania (ENA)